Usulan Perbaikan Dalam Meminimasi Waste Pada Aktivitas Proses Produksi Box HP Oppo Dengan Konsep Lean Manufacturing Menggunakan Metode Value Stream Mapping (VSM) - Sutaarga, Ossa; Maulana, Hilmi (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2022)
PT. Satyamitra Kemas Lestari, Tbk is a company engaged in the packaging industry for HP oppo cartons / boxes. PT. Satyamitra Kemas Lestari, Tbk in its activities always try to maintain and improve the quality and production capacity, but in every effort to achieve this the company is often faced with various kinds of obstacles. The obstacle faced from this research is that there are activities / activities that are waste in the HP Oppo box production process, one of which is the time for setting the machine and transferring goods from one process to the next which takes quite a long time. This condition is contrary to requests from customers that must be fulfilled on time, so that it affects production targets and causes a gap of an average of 6% between production targets and production results in the period March - August 2021. From one of these problems PT. Satyamitra Kemas Lestari will improve the production system by streamlining or eliminating one process that is deemed unnecessary or can be combined with other processes. This study aims to find out what waste occurs in the HP Oppo box production process at PT. Satyamitra Kemas Lestari. From the results of this study, by using the Value Stream Mapping (VSM) method, the waste that occurs can be determined, so that suggestions for improvements can also be made to reduce waste. From the proposed improvement given by the author, the resulting percentage comparison of the results of the lead time before and after the repair. It can be seen that there is a time difference resulting from the previous process. The production process becomes faster or the time reduction that occurs from the previous 424.34 minutes to 301.04 minutes, there has been a reduction in time of 123.3 minutes or a waste reduction of 29.05%. hp oppo box production process, so that the specified target can be achieved and the production process time becomes more efficient.Keywords: HP oppo box, Waste, Production Process, Production Target, Value Stream Mapping.